First‐pass myocardial perfusion MRI with reduced subendocardial dark‐rim artifact using optimized Cartesian sampling. Issue 2 (17th August 2016) - Zhou, Zhengwei; Bi, Xiaoming; Wei, Janet; Yang, Hsin‐Jung; Dharmakumar, Rohan; Arsanjani, Reza; Bairey Merz, C. Noel; Li, Debiao; Sharif, Behzad
Abstract : Purpose: The presence of subendocardial dark‐rim artifact (DRA) remains an ongoing challenge in first‐pass perfusion (FPP) cardiac magnetic resonance imaging (MRI). We propose a free‐breathing FPP imaging scheme with Cartesian sampling that is optimized to minimize the DRA and readily enables near‐instantaneous image reconstruction. Materials and Methods: The proposed FPP method suppresses Gibbs ringing effects—a major underlying factor for the DRA—by "shaping" the underlying point spread function through a two‐step process: 1) an undersampled Cartesian sampling scheme that widens the k ‐space coverage compared to the conventional scheme; and 2) a modified parallel‐imaging scheme that incorporates optimized apodization ( k ‐space data filtering) to suppress Gibbs‐ringing effects. Healthy volunteer studies ( n  = 10) were performed to compare the proposed method against the conventional Cartesian technique—both using a saturation‐recovery gradient‐echo sequence at 3T. Furthermore, FPP imaging studies using the proposed method were performed in infarcted canines ( n  = 3), and in two symptomatic patients with suspected coronary microvascular dysfunction for assessment of myocardial hypoperfusion. Results: Width of the DRA and the number of DRA‐affected myocardial segments were significantly reduced in the proposed method compared to the conventional approach (width: 1.3 vs. 2.9 mm, P < 0.001; number of segments: 2.6 vs. 8.7; P < 0.0001). The number of slices with severe DRA was markedly lower for the proposed method (by 10‐fold). The reader‐assigned image quality scores were similar ( P  = 0.2), although the quantified myocardial signal‐to‐noise ratio was lower for the proposed method ( P < 0.05). Animal studies showed that the proposed method can detect subendocardial perfusion defects and patient results were consistent with the gold‐standard invasive test. Conclusion: The proposed free‐breathing Cartesian FPP imaging method significantly reduces the prevalence of severe DRAs compared to the conventional approach while maintaining similar resolution and image quality. Level of Evidence: 2 J. Magn. Reson. Imaging 2017;45:542–555.